2009
DOI: 10.1111/j.1600-0404.1984.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathy and motor neuron syndromes associated with plasma cell disease

Abstract: Increasing numbers of patients are being recognized with neurological abnormalities associated with the immunochemical changes of plasma cell disease. To illustrate the wide spectrum of clinical disorders that can be found, I discuss in detail 5 patients: 2 with neuropathy, 3 with amyotrophic lateral sclerosis (ALS), all of whom had serum monoclonal paraproteinemia. In addition, I report in tabular form 6 patients with paraproteinemia and the following clinical presentations: 1) systemic lupus with polyneuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The association between MND and LPD could be coincidental, but LPD seems to be disproportionately frequent in patients with MND compared to the population in general [5]. Despite an initial report suggesting that major improvements occurred sometimes coincidentally with reductions in paraprotein levels using prednisone, cyclophosphamide, chlorambucil and plasma exchange treatments even in some patients who had the clinical appearance of ALS [6], most of the subsequent literature argues against this, with less than successful trials using various immunomodulatory agents and plasma exchange. Gordon et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between MND and LPD could be coincidental, but LPD seems to be disproportionately frequent in patients with MND compared to the population in general [5]. Despite an initial report suggesting that major improvements occurred sometimes coincidentally with reductions in paraprotein levels using prednisone, cyclophosphamide, chlorambucil and plasma exchange treatments even in some patients who had the clinical appearance of ALS [6], most of the subsequent literature argues against this, with less than successful trials using various immunomodulatory agents and plasma exchange. Gordon et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, Latov [10] found 19 cases of MND and monoclonal gammopathy. Patten [6] described four patients with ALS and IgG monoclonal gammopathy. Shy et al .…”
Section: Discussionmentioning
confidence: 99%